Riots and rioters in Belfast - demographic analysis of 1,674 arrestees in a 2-year period - Lyons, HA (Economic & Social Studies, 1972)
Rioting has been a feature of Belfast life for the past 150 years. Prior to 1832, civil disturbances were commoner in rural areas (Broeker 1970). Severe rioting has occurred in the years 1832; 1835; 1843; 1852; 1857; 1864; 1872; 1880; 1886; 1898; 1907; 1912; 1920-22; 1935 and 1964. Some of these disturbances, have been studied in considerable detail by official Commissioners of Enquiry (1857; 1886). Others have been described by authors such as Henry (1864), Boyd (1969) and King (1965).
Keywords: Riots; Belfast; Demographic Analysis